Availability of black soldier fly meal as an alternative protein source to fish meal in red sea bream (Pagrus major, Temminck & Schlegel) fingerling diets. (25th August 2021) - Takakuwa, Fumiaki; Tanabe, Ryota; Nomura, Shohei; Inui, Takashi; Yamada, Shinichi; Biswas, Amal; Tanaka, Hideki
Abstract: Black soldier fly meal (BM) is an outstanding candidate as a fish meal (FM) substitute because it contains relatively high protein and essential amino acids. In this study, we replaced FM in red sea bream diets ( Pagrus major ) with BM to investigate its effect on growth and feed utilization. Six isonitrogenous and isolipidic experimental diets were prepared by substituting 0%, 20%, 40%, 60%, 80% and 100% FM protein with BM (Control, BM20, BM40, BM60, BM80 and BM100, respectively). After the 8‐week feeding trial, final body weight, weight gain, specific growth rate and feed efficiency decreased linearly with increasing dietary BM level ( p  < 0.05). Apparent digestibility of protein and fat and serum total cholesterol concentration decreased with increasing dietary BM levels ( p  < 0.05) Final body weight, WG, SGR and FE against dietary BM level had breaking points of 76.2%, 41.7%, 76.5% and 60.0%, respectively, in segmental regression analysis. In conclusion, the results suggest that BM can replace a maximum of 41.7% of FM in the diet of red sea bream without compromising growth performance or feed efficiency for 56 days.